Geotechnical Behaviour of Reinforced Soft Clay by Marble Dust as a Waste Material - Mohamed Elsiragy (Journal of Engineering Research - Egypt, 2021)
Civil engineers around the world are in search of new alternative resources which are required both for cost-effective solutions for ground improvement and conservation of scarce natural resources. The various methods of ground improvement currently in use include lime columns, stone columns, use of chemical stabilizers, and various kinds of inclusions like metal strips, mats, fibres, geosynthetics, etc. The cost of these virgin materials as well as the processes involved is usually high and as such, they are yet to be commonly used in developing foundation performances. This paper illustrates the application of using marble dust stabilization in improving the soft clay soil. Various tests with different marble dust contents were performed to study the effect of using material as a stabilizing technique on main geotechnical soft clay properties. A series of laboratory tests like plasticity and consolidation at a different percentage of marble dust has been done. These experiments showed that the addition of marble dust resulting in composites hardens material which reduced the plasticity and compressibility parameters of the reinforced soft clay. The induction of reinforced composite material successfully decreases and adsorbs the excess water inside the soft clay thus, modifying the soft clay plasticity and significantly increase the soft clay stiffness and decrease the settlement. The used marble dust reducing the volumetric shrinkage and produced isotropic compressible ductile material with less settlement and higher shear strength. This adopted method will be applied to unravel the geotechnical stabilization issues, for instance, road embankments modification and foundation use.